Mechanical-Thermal Coupling and Deformation Mechanisms of Cellular High-Entropy Alloy Lattice Structures Under Elevated Temperatures - Shuai Tong; Guoxiang Shen; Zhengchen Han; Zhichao Ma; Hongwei Zhao; Luquan Ren; Chuliang Yan (Chemical and Materials Sciences: Developments and Innovations Vol. 8, 2024)
The lattice structures were a novel applied structure based on lightweight design, which had potential applications in industrial fields such as turbomachinery, aerospace, and automotive. To investigate the effect of elevated temperature service conditions on the compressive strength of CoCrFeMnNi high entropy alloy with lattice structures prepared by powder bed fusion, the mechanical properties of the lattice structures at a temperature in a range from 20oC to 900oC were obtained through a self-developed in-situ mechanical-thermal coupling compressive system. The real-time deformation behaviors of the lattice structures were observed by an optical-infrared dual-spectrum imaging system. The experimental results indicated that the compressive strength, structural stiffness, and energy absorption of the specimens increased with the increasing temperature ranging from 20oC to 600oC during the load-bearing stage, accompanied by a fracture mode from cleavage step to dimple. At an elevated temperature of 900oC, the specimens exhibited the lowest compressive strength and structural stiffness but the highest densification strain. Significantly, the temperature-dependent deformation behaviors were revealed, as the gradually increased temperature promoted the deformation failure behavior transforming from “layer by layer” to a “45o shear band”. The improved plasticity at elevated temperatures enhanced the deformation capacity of lattice structures, released the local concentrated load and effectively weakened the stress concentration. The above research indicated that the designed lattice structures were suitable for extreme working conditions such as aerospace or automotive, due to their excellent elevated temperature service performance.